IMPROVING FUTURE PREVENTIVE CARE THROUGH EDUCATIONAL EFFORTS AT A WOMEN’S COMMUNITY SCREENING PROGRAM - Carney, Patricia; Dietrich, Allen J.; Freeman, Daniel H. (Journal of community health, 1992)
Cervical cancer mortality continues to be a significant problem in the United States. Pap Test screening programs have been effective in attracting high risk women, but the impact of these programs on subsequent health care has seldom been explored. This follow up study examined the impact of a cervical cancer screening and education program on preventive health behaviors of New Hampshire women in the 24 months following the screening program. A mailed survey was sent to a random sample of 750 women from program participants to evaluate both their recent preventive health care practices and to identify perceived barriers to obtaining preventive health services. Of these, 71.1 percent responded. Survey responses of the original program participants were linked to each subject’s previous answers to the same questions asked 24 months earlier. A comparison group was derived by asking follow up study participants to identify a female acquaintance within five years of her age. Seventy-four percent of the comparison group responded. Survey responses of original program participants were then compared to those of the comparison group. Results indicate that women who participated in the original Project received significantly more preventive health care services in the two years since the Project than in the two years prior to it. Women in the comparison group received more Paps and clinical breast examinations than women in the participant group, perhaps because all participants had received a Pap test two years before. Having a regular health care provider was the most significant characteristic associated with obtaining indicated preventive services. An important contribution of community screening programs may be to encourage women to establish a regular source of care.